2020
DOI: 10.7819/rbgn.v22i1.4038
|View full text |Cite
|
Sign up to set email alerts
|

Millennial Consumer Preferences in Social Commerce Web Design

Abstract: Purpose-Considering the context in which social commerce has changed the way consumers search for information and share experiences, the objective of this study is to understand how three factors of web design (usability, functionality, and sociability) influence consumers' cognitive and affective assessments and affect their intention to buy. Design/methodology/approach-Using the PLS technique on a sample of 230 millennials who are regular social commerce users, this study is adapted to the social context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
(103 reference statements)
1
5
0
4
Order By: Relevance
“…Design is also essential in determining consumer perceptions and behavior (Liang & Lai, 2002;Wolfinbarger & Gilly, 2003). For this reason, companies must be able to guarantee a website with a quality design to invite consumers and make purchases (Anaya-Sánchez et al, 2020;Fan & Tsai, 2010;Liang & Lai, 2002).…”
Section: Web Designmentioning
confidence: 99%
“…Design is also essential in determining consumer perceptions and behavior (Liang & Lai, 2002;Wolfinbarger & Gilly, 2003). For this reason, companies must be able to guarantee a website with a quality design to invite consumers and make purchases (Anaya-Sánchez et al, 2020;Fan & Tsai, 2010;Liang & Lai, 2002).…”
Section: Web Designmentioning
confidence: 99%
“…Thus, social relationships and interactions are a distinguishing characteristic of s-commerce when compared to traditional e-commerce (H. Zhang et al, 2014;Friedrich et al, 2016). Social interactions and relationships among consumers can impact the intention to buy as well as the trust of consumers in s-commerce (Yahia et al, 2018;Anaya-Sánchez et al, 2020;Fang & Li, 2020;Handarkho, 2020;Nadeem et al, 2020). Furthermore, previous research revealed that sociability has a statistically significant positive direct effect on the intention to purchase by consumers in scommerce (Rashid et al, 2020;Hsiao, 2021).…”
Section: Sociabilitymentioning
confidence: 97%
“…Meanwhile, organism is an intervening variable in the SOR model (Donovan & Rossiter, 1982). The organism is operationalized as affective states, which are usually associated with feelings and emotions that the individual experiences as a result of the stimuli (Anaya-Sánchez et al, 2020).Finally, the response is the final action that results from the individual's reaction, including psychological reactions such as attitudes and behavioral responses (Bagozzi, 1986).…”
Section: Literature Review Stimulus -Organism -Response Theorymentioning
confidence: 99%
“…Moreover, previous studies have demonstrated that experience could be a large variable in the transmission of the stimulus cue to influence behavioral intention. In these studies, experience is empirically found to be a major mediating variable between website characteristics and behavioral intention (Anaya-Sánchez et al, 2020;Salehi-Esfahani & Kang, 2019).…”
Section: H3: User Experience Has a Positive Influence On Donation Int...mentioning
confidence: 99%